Dual Role of Dietary Curcumin Through Attenuating AFB1-Induced Oxidative Stress and Liver Injury via Modulating Liver Phase-I and Phase-II Enzymes Involved in AFB1 Bioactivation and Detoxification - Muhammad, Ishfaq; Wang, He; Sun, Xiaoqi; Wang, Xinghe; Han, Meiyu; Lu, Ziyin; Cheng, Ping; Hussain, Muhammad A.; Zhang, Xiuying (Frontiers in Pharmacology, 2018)
It is well understood that liver cytochrome p450 enzymes are responsible for AFB1 bioactivation. While, phase-II enzymes regulated by the transcription factor nuclear factor-erythroid-2-related factor 2 (Nrf2) involved in detoxification of AFB1. In this study, we explored the potential of curcumin to prevent AFB1-induced liver injury by modulating liver phase-I and phase-II enzymes along with Nrf2 involved in AFB1 bioactivation and detoxification. Arbor Acres broiler were divided into four groups including control group (G1; fed only basal feed), curcumin alone-treated group (G2; 450 mg/kg feed), AFB1-fed group (G3; 5 mg/kg feed), and curcumin plus AFB1 group (G4; 5 mg AFB1+450 mg curcumin/kg feed). After 28 days, liver and blood samples were collected for different analyses. Histological and phenotypic results revealed that AFB1-induced liver injury was partially ameliorated by curcumin supplementation. Compared to AFB1 alone-treated group, serum biochemical parameters and liver antioxidant status showed that curcumin supplementation significantly prevented AFB1-induced liver injury. RT-PCR and western blot results revealed that curcumin inhibited CYP enzymes-mediated bioactivation of AFB1 at mRNA and protein level. Transcription factor Nrf2 and its downstream genes such as GSTA3 and GSTM2 mRNA and protein expression level significantly up-regulated via dietary curcumin. In addition, GSTs enzyme activity enhanced with dietary curcumin which plays a crucial role in AFB1-detoxification. Conclusively, the study provided a scientific basis for the use of curcumin in broiler`s diet and contributed to explore the multi-target preventive actions of curcumin against AFB1-induced liver injury through the modulation of phase-I and phase-II enzymes, and its potent anti-oxidative effects.